Monotherapy with a novel intervenolin derivative, AS‐1934, is an effective treatment for Helicobacter pylori infection. Issue 2 (28th February 2018) - Ohishi, Tomokazu; Masuda, Tohru; Abe, Hikaru; Hayashi, Chigusa; Adachi, Hayamitsu; Ohba, Shun‐ichi; Igarashi, Masayuki; Watanabe, Takumi; Mimuro, Hitomi; Amalia, Eri; Inaoka, Daniel Ken; Mochizuki, Kota; et al.
Abstract: Background: Helicobacter pylori ( H. pylori ) infection causes various gastrointestinal diseases including gastric cancer. Hence, eradication of this infection could prevent these diseases. The most popular first‐line treatment protocol to eradicate H. pylori is termed "triple therapy" and consists of a proton pump inhibitor (PPI), clarithromycin, and amoxicillin or metronidazole. However, the antibiotics used to treat H. pylori infection are hindered by the antibiotics‐resistant bacteria and by their antimicrobial activity against intestinal bacteria, leading to side effects. Therefore, an alternative treatment with fewer adverse side effects is urgently required to improve the overall eradication rate of H. pylori . Objective: The aim of this study was to assess the effectiveness and mechanism of action of an antitumor agent, intervenolin, and its derivatives as an agent for the treatment of H. pylori infection. Results: We demonstrate that intervenolin, and its derivatives showed selective anti‐ H. pylori activity, including antibiotic‐resistant strains, without any effect on intestinal bacteria. We showed that dihydroorotate dehydrogenase, a key enzyme for de novo pyrimidine biosynthesis, is a target and treatment with intervenolin or its derivatives decreased the protein and mRNA levels of H. pylori urease, which protects H. pylori against acidic conditions in the stomach. Using a mouse model of H. pylori infection, oral monotherapy with the intervenolin derivative AS‐1934 had a stronger anti‐ H. pylori effect than the triple therapy commonly used worldwide to eradicate H. pylori . Conclusion: AS‐1934 has potential advantages over current treatment options for H. pylori infection.